Faceworld the face in the twenty-first century - Zilio, Marion 1984- (Polity, 2020)
"We have long accepted the face as the most natural and self-evident thing, as if the face were the public manifestation of our inner being. Nothing could be further from the truth. Rather than a window opening onto our inner nature, the face has always been a technical artefact-a construction that owes as much to artificiality as to our genetic inheritance. From the origins of humanity to the triumph of the selfie, Marion Zilio charts the history of the technical, economic, political, legal, and artistic fabrication of the face. Her account of this history culminates in a radical new interrogation of what is too often denounced as our contemporary narcissism. In fact, argues Zilio, the "narcissism" of the selfie may well reconnect us to the deepest sources of the human manufacture of faces-a reconnection that would also be a chance for us to come to terms with the non-human part of ourselves"--
Keywords: Geschichte 2000-; Selbstbild; Wahrnehmung; Gesicht -- Motiv; Bildnis; Ästhetik; Gesicht; Face / Social aspects; Face perception; Facial expression